Efeito dos íons Ni2+ nas propriedades estruturais, ópticas e morfológicas do tungstato de prata - Pereira, Wyllamanney da Silva (2015)
The tungstates are important compounds and known for their optical properties. In this work, solid solutions with nickel silver tungstate, 𝐴𝑔2−2𝑥𝑁𝑖𝑥𝑊𝑂4, compositions (0, 01 ≤ 𝑥 ≤ 0, 08) were synthesized by the hydrothermal method of microwave to 140 ° C for 1 h, and to assess the influence of 𝑁𝑖2+ ions in the structural, morphological and photoluminescent of the silver tungstate (𝐴𝑔2𝑊𝑂4). Materials 𝐴𝑔2−2𝑥𝑁𝑖𝑥𝑊𝑂4 (0 ≤ 𝑥 ≤ 0.08) were characterized by X-ray diffraction (XRD), spectroscopy micro-Raman (MR) and absorption in the Infrared (IR) region. The scanning electron microscopy (SEM) was used for image recording surface of these ceramic oxides, while the energy dispersive X-ray technique (EDS) with mapping of chemical elements, was used to qualitatively determine the chemical composition of the samples. The optical properties were studied by electron spectroscopy in the region of ultraviolet-visible (UV-vis) in which the values of energy band gap (𝐸𝑔𝑎𝑝) were estimated, and by means of photoemission spectroscopy was studied effect of 𝑁𝑖2+ ions in photoluminescence (PL) of silver tungstate. The XRD patterns of the single-phase crystallization of all samples in the orthorhombic structure of the silver tungstate and they have indicated a long range structural order. Small changes in network parameters and atomic coordinates, indicate the existence of distortions on the cluster [𝐴𝑔𝑂𝑛] (𝑛 = 2, 4, 6 and 7) and [𝑊𝑂6] and inserting the 𝑁𝑖 atoms in the crystal lattice 𝛼-𝐴𝑔2𝑊𝑂4. Changes in MR spectra and peak detection regarding 𝑁𝑖 − 𝑂 bond in IR spectra of solid solutions suggest the introduction of 𝑁𝑖 atoms in the 𝐴𝑔2𝑊𝑂4 network.The SEM images showed that the ions 𝑁𝑖2+ were able to modify the morphology of silver tungstate microcrystals, in the studied conditions. The EDS spectra and map images indicated that all materials are composed of the elements 𝐴𝑔, 𝑊 and 𝑂, as expected. They also noted the presence of 𝑁𝑖 element in the composition of solid solutions. The values of 𝐸𝑔𝑎𝑝 estimated by means of UV-vis spectra suggest the existence of intermediate states in the forbidden area, from structural defects. The changes in spectra of PL samples indicated that the 𝑁𝑖 atoms alter the effect of the order-disorder, and the average distance favored over energy emissions associated with shallow defects.